School-to-work transition in Chile and Uruguay from the education-occupation linkage perspective - Agustina Marques Hill; Heike Solga (Advances in Life Course Research, 2025)
This study examines school-to-work transitions (STWTs) in Chile and Uruguay, focusing on education-occupation linkages. For the first time, we apply the linkage strength approach to Latin American countries, using cross-sectional household survey data. Since STWT research is highly segregated across the different world regions, we do so in a comparative perspective with France, Germany, and the United States. Although Chile and Uruguay are high-income countries, they still face STWT challenges common to Latin America, such as high levels of informal and agricultural work. However, Chile has higher educational attainment than Uruguay, similar to the comparison countries. Our analysis reveals strong education-occupation linkages not only among higher qualified young adults, but also among low-qualified entrants – thus a “linkage trap” into low-skilled jobs – in Chile and especially in Uruguay. Moreover, unlike in France and Germany, general education provides stronger linkages than vocational programs. Informal employment does not differ significantly from formal employment in terms of linking education to occupations in STWTs. In fact, informal employment is associated with stronger linkages for low-qualified young workers in Uruguay. Furthermore, in Uruguay, strong linkages are associated with lower earnings for both tertiary and less-educated entrants, challenging the positive interpretation of high linkage strength drawn from the comparison countries. Overall, the linkage strength patterns are not as different across the different world regions: Chile's and Uruguay's patterns are in some aspects closer to France and Germany than the United States is to either European country.
Keywords: 370; school-to-work transition; linkage strength; mismatches; gender differences; Latin America